2009
DOI: 10.1016/j.cub.2008.11.068
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydomonas CAV2 Encodes a Voltage- Dependent Calcium Channel Required for the Flagellar Waveform Conversion

Abstract: Cilia and flagella can alter their beating patterns through changes in membrane excitation mediated by Ca(2+) influx. The ion channel that generates this Ca(2+) influx and its cellular distribution have not been identified. In this study, we analyzed the Chlamydomonas ppr2 mutant, which is deficient in the production of a flagellar Ca(2+) current and consequently has a defective photophobic response and mechanoshock response. ppr2 had a mutation in CAV2, which encodes a homolog of the alpha(1) subunit of volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
3
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 32 publications
1
88
3
1
Order By: Relevance
“…This accumulation is similar to the accumulation of the PKD-2::GFP polycystin fusion protein observed at the ciliary base of the CEM male sensory neurons in Kinesin-II and the klp-6 kinesin-3 mutant backgrounds Peden and Barr, 2005). It has been suggested and/or shown that IFT plays a role in regulating ciliary abundance of membrane proteins such as PKD-2 in C. elegans cilia, and PKD2 and the CAV2 Ca 2+ channel in Chlamydomonas flagella Fujiu et al, 2009;Huang et al, 2007;Qin et al, 2001;Qin et al, 2005), although similar to observations reported here, no movement of PKD-2 has been observed in C. elegans sensory cilia (Qin et al, 2005). The absence of significant recovery of CNG channel fusion protein fluorescence in AWB and ASK cilia upon photobleaching the middle segments argues against a requirement for IFT in maintaining ciliary localization of these channels in these domains under the examined conditions.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This accumulation is similar to the accumulation of the PKD-2::GFP polycystin fusion protein observed at the ciliary base of the CEM male sensory neurons in Kinesin-II and the klp-6 kinesin-3 mutant backgrounds Peden and Barr, 2005). It has been suggested and/or shown that IFT plays a role in regulating ciliary abundance of membrane proteins such as PKD-2 in C. elegans cilia, and PKD2 and the CAV2 Ca 2+ channel in Chlamydomonas flagella Fujiu et al, 2009;Huang et al, 2007;Qin et al, 2001;Qin et al, 2005), although similar to observations reported here, no movement of PKD-2 has been observed in C. elegans sensory cilia (Qin et al, 2005). The absence of significant recovery of CNG channel fusion protein fluorescence in AWB and ASK cilia upon photobleaching the middle segments argues against a requirement for IFT in maintaining ciliary localization of these channels in these domains under the examined conditions.…”
Section: Discussionsupporting
confidence: 77%
“…In Drosophila mechanosensory organs, a TRPN channel required for primary mechanotransduction is localized to the distal ciliary region, whereas TRPV channels that regulate signal amplification are instead localized to a proximal zone (Cheng et al, 2010;Lee et al, 2010;Liang et al, 2011). Similarly, the PKD-2 polycystin 2 channel is enriched in the proximal regions of male sensory neuron cilia in C. elegans Barr et al, 2001;Barr and Sternberg, 1999), and signaling proteins are also localized non-uniformly in Chlamydomonas flagella (Fujiu et al, 2009;Iomini et al, 2006). Thus, differential clustering of signaling molecules to specific sensory cilia subdomains could be a general mechanism to increase response sensitivity and fidelity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is clear that multiple losses of Ca V s have occurred in other lineages such as land plants (Verret et al, 2010). However, the presence of Ca V s in green algae by itself is sufficient to strongly suggest that these channels were already present in the common ancestor of plants and animals (Fujiu et al, 2009;Verret et al, 2010). Alternatively, one can hypothesize that this extremely patchy distribution is the result of an ancient horizontal gene transfer, but we could not find supporting evidence for such a scenario.…”
Section: Reviewcontrasting
confidence: 60%
“…Phylogeny reveals that NvErg1 and the mammalian channels represent the ancestral electrical behavior, whereas NvErg4 evolved in a convergent manner to the Drosophila channel. Surprisingly, it seems that nematode Erg channels also acquired this feature independently, suggesting that this electrical behavior evolved at least three times during animal evolution (Martinson et al, 2014).Voltage-gated calcium channels: a widely, yet sparsely, distributed channel family Ca 2+ currents are associated with locomotion via flagellar movements in paramecium (Plattner, 2014) and algae (Chlamydomonas) (Wakabayashi et al, 2009;Fujiu et al, 2009), stress responses in diatoms (Vardi et al, 2006), protein secretion, motility differentiation and infection in parasitic protozoa (Moreno and Docampo, 2003;Nagamune et al, 2007) and light emission in dinoflagellates (von Dassow and Latz, 2002). Hence, it would seem that four-domain Ca V s would be widespread in protozoa.…”
mentioning
confidence: 99%
“…In addition, all displayed similar phototaxis to a narrow light beam parallel to the glass surface, a method of assaying phototaxis under a microscope (38). Furthermore, all exhibited photoshock in response to a flash of strong white light (22,38). We reasoned that the irregular trajectory of RSP2 1-120 cells might be a different response in which light drove them toward the perpendicularly oriented glass surface under regular microscopes.…”
Section: Fig 6 Truncated Rsp2 Polypeptides Restored Rs Composition (mentioning
confidence: 97%